LINGUOCULTURAL AND PRAGMATIC ASPECTS OF PRECEDENT PHENOMENA: TRANSLATOLOGICAL PECULIARITIES - Tatyana V. Marchenko (Вестник Северо-Кавказского федерального университета)
The article highlights the translation peculiarities of precedent phenomena within mass-media discourse. The adequacy of translation modifications and the use of pragmatic adaptation are scrutinized.